SPECIES DIVERSITY, PEST STATUS, INTRASPECIFIC COMPETITION, AND CONTROL OF TERMITE (INSECTA: ISOPTERA) IN THE CITY OF BANDUNG - Kuswanto, Eko
Development and implementation of environmental friendly termite control program has been increasing due to public concern on environment health. In order to developed said program, understanding on biology of termites, i.e taxonomy, population distribution, behaviour, and other biology characteristic of target termite, is crucial to improve success rate of control program. Based on this concern, purpose of this study are [1] to acquire data on species diversity of termites in Bandung City (as study area), [2] to determine pest status of termite population found in residential are in Bandung City; [3] to understand respon of Macrotermes gilvus to various commercial cellulosic materials; [4] to gather information on M. gilvus intraspecific competition and identification of speciesspecific chemistry components; and [5] To conduct a review on the effort of termite control in Bandung City. Research was divided into three stages and conducted since March 2012 to June 2015 in Bandung City. At first stage, 400 houses and 50 lots for housing, represented total house building in Bandung were surveyed. The selection of house samples was conducted by stratified random sampling method based on the level of building density of 30 districts in Bandung City. Termites collected from the location of observation were preserved in vials with alcohol of 85%. Identification of termite based on observation of external morphology of adult and soldier caste), with Leica M205C stereo microscope and the enteric valve armature (especially for worker caste of family Termitidae), with Leica CTR5500 stereo microscope. Location, where sample was collected, marked in the map by ArcGIS version 10 to create distribution map of each termite species in Bandung. In order to test the hypothetic termite dispersal route and evaluate their importance as pest of housing are in Bandung city, the diversity of termites in their natural habitat, in Taman Hutan Raya Juanda,Lebak Siliwangi area, and Bandung Zoo were observed. At second stage, response of termites M. gilvus to twelve types of wooden and four cellulosic materials (plywood, gypsum, laminated wood, and wall paper) building materials was observed for one week. The result was analysed to determine the Damage Rate Index (DRI) and Material Resistance Index (MRI). During this stage intraspecific competition M. gilvus colonies originated from Bandung, Bogor, and Bandar Lampung was observed. vi As many as 45 combinations of treatment from three different colonies were tested in the test area and was taped for five minutes using Ricoh4WG. The result was analyzed to determine the level of agonistic behavior. In order to strengthen the information on the intra species competition, chemical compound of volatile produced by worker and soldier (minor and major) of tested colonies was identified by gas chromatography mass spectra (GCMS). At the third stage, questionnaires was sendto registered pest control companies in Bandung in order to understand level of termite control conducted in Bandung. The result showed that 38.75% of buildings in Bandung City were infested by termites. Five species of three families were identified from samples, Cryptotermes dudleyi Banks [Kalotermitidae]; Coptotermes gestroi (Wasmann) [Rhinotermitidae]; Ancistrotermes pakistanicus Ahmad, Macrotermes gilvus Hagen, and Odontotermes javanicus Holmgren [Termitidae]. Cr. dudleyi and M. gilvus were widely distributed (each in 26 and 19 districts, respectively). Subterranean termites Co. gestroi, although only found in one district (Lengkong), was recorded for the first time in housing area in Bandung. The revision of research method by stratified random sampling, for determine sample sizes and area, played a huge role to improve quality of sample which provide better realistic condition found in the field. Based on the analysis of six variables, Cr. dudleyi, M. gilvus, and Co. gestroi termites considered as pests in urban environment in Bandung City. Among those species, M. gilvus, the level of pest was improve as they also found in natural habitat of Bandung provide constant treat to housing areas. Based on distribution of termite species, hypotheses of dispersal route of termites in Bandung was developed as follows: M. gilvus migrated from natural habitat, located at higher elevation, to housing area locate at lower area may explain extensive invasion of M. gilvus in Bandung City. Drywood termites Cr. dudleyi probably invade through through mobilization of building materials for outside Bandung city while Co. gestroi termites also suspected to have come from outside Bandung however limited on in Lengkong area through by some environmental factors. The response of 16 commercial cellulosic materials (12 types of sold wood and 4 cellulosic materials) showed that wooden building material sold in Bandung considered resistant and sufficiently resistant to M. gilvus, while level of resistance to M. gilvus of four cellulosic materials was extremely resistant (plywood and wall paper), resistant (gypsum), and extremely unresistant (laminated wood). It is quite surprising that laminated wood protected with antitermite was in fact categorized into extremely unresistant to M. gilvus. Therefore, resistance of cellulosic materials to M. gilvus should be considered during application of these materials for aesthetic use. Agonistic behavior did not showed in M. gilvus both inter- and intracolony. Agonistic test towards the three termite colonies M. gilvus from Bandung, Bogor, and Bandar Lampung with a maximum distance of 216 km did not indicated presence of agonistic behavior. The agonistic level in intracolony only showed examination/antennation, while in intercolony it showed examination/antennation and alarm behavior and avoidance one another. The behavior of aggression (as vii behavior that signals the presence of agonistic behavior) did not appear either in inter- or intracolony. Identification towards volatile component suspected to play a role as the key of intraspecific colony recognition using GC-MS analysis resulting in 22 volatile components from worker and soldier castes (either minor or major). Volatile components (Z)-6-Octadecenoic acid and (E)-9-Octadecenoic acid were suspected to have a role as the key for recognizing both non- and nestmember s of M. gilvus. From as many as 17 pest control companies officially registered in DPD ASPPHAMI West Java year 2014, about 10 companies cater for the service of termite control. The service of antitermite contributes about 25% of total revenue with the average number of jobs per year reaching 99.6 unit jobs per company. The potential antitermite jobs in Bandung City only reached approximately 1/3 of the projection of 1% of the total estimation of house buildings infested with termites in Bandung City in 2012. The estimation of antitermite job value reached Rp13.5 billion, and will continue to increase to Rp 45 billion in 2017, Rp99 billion in 2022, and Rp 180 billion in 2027.